Macroeconomic Effects of Prelected Population Aging in Industrial Countries - Masson, Paul.; Tryon, Ralph (Washington, D.C. : International Monetary Fund, 1990)
The effects of population aging are examined with the aid of a theoretical model and simulations of MULTIMOD. An older population will consume more of aggregate disposable income, require higher government expenditure, and decrease labor supply. These effects should raise real interest rates and lower the capital stock and output. Effects on current balances will depend on the relative speed and extent of aging. Simulations of projected demographic changes suggest that by 2025, real interest rates would be increased by several percentage points and net foreign assets increased in the United States, and decreased in Japan and Germany, as a result.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet